DER BEGRIFF DER PSYCHISCHEN KRENKHEIT AUS DER SICHT DER FICHTESCHEN TRANSZENDENTALPHILOSOPHIE - Hoff, Paul (Daimon Revista Internacional de Filosofia, 1994)
Psychiatry’s relationship with philosophy is much closer than one might think if applying a narrow dichotomy between natural sciences and the humanities. In first step, the paper discusses this relationship with regard to Karl Jaspers’ critical arguments in his General Psychopatology (1913). Then, in its main part, I try to develop the fundamental principles of transcendental philosophy as proposed by Kant and Fichte and to prove their importance for basic psychiatric questions. It can be shown that psychiatry is specially at risk to follow dogmatical empiricism as well as dogmatical idealism. Both are clearly rejected be transcendental philosophy, which provides an adequate theoretical link between the three necessary levels of empirical and teleological finding and teh individual person. Two concepts that are of central importance for any psychiatric application, are highly typical for Fichte’s philosophy, the idea of freedom and the crucial role of interpersonality.